Students’ Voice of Listening Activities Using English Popular Songs - Rossanti Dewi; Testiana Deni Wijayatiningsih; Riana Eka Budiastuti (ETERNAL (English Teaching Journal), 2020)
Listening is one of the skills in learning English. The 11th grade students of IPA 1 SMA N 15 Semarang had low ability in listening. Therefore, this research was done in order to know the response of the 11th grade students of IPA 1 SMA Negeri 15 Semarang in English learning by doing listening a song as the media. The object of this research is the 11th grade students of IPA 1 SMA Negeri 15, Semarang. It is a descriptive qualitative study which employed observation and interview. The results showed that the 11th grade students of IPA 1 SMA Negeri 15 Semarang like to do listening activities, but they still had less exercises in listening to songs or watching English movies.